(untitled) (Fiep Bulletin - online, 2017)
Dancing is a way of seeing oneself and seeing the world, to feel your body and use it to experience other feelings. Thebody is a vehicle of expression, communication, concern and understanding of reality. The artistic manifestations appear aspropellants of that vehicle and result as a resource to assist in the formation of the individual, treating the body as a whole. Thus,our goal was to take the dance as an artistic-expressive-educational demonstration to the youth of Alto do Moura, contributing totheir training and demystifying / deconstructing prejudices related to dance. Children and teenagers from the age group between10 and 17 years old of both genres were the target audience, totaling 30 participants. Classes were held in the Club of Craftsmenin Barro Alto and Moura Residents lasting 2 hours a week. There was application of survey to the participants of the dance project,in order to know who they were, as well as their desires and cultural and artistic interests. Group dynamics, motion sequences,choreography creation and improvising were experienced in class in order to develop corporal expression and awareness, towork on interaction with others and with the space, respecting diversity and stimulating creativity. The project culminated in thedevelopment of choreographies, with the participation of the children and adolescents in events organized by the partnerorganization and the Institute itself. We conclude that the dance has brought many contributions to the education of thesechildren and adolescents, enriching interaction, artistic imagination and expanding the horizons of artistic and expressivelanguage, and you can deconstruct prejudices related to dance and gender.